Systematic literature review: Community Capacity Building Collaborative Model as an Earthquake and Tsunami Disaster Mitigation Effort - Roni Ekha Putera; Tengku Rika Valentina; Nika Saputra; Rizki Afri Mulia; Tirza Haqia Purnama (Universitas Sultan Ageng Tirtayasa, 2025)
The purpose of this article is to conduct a literature review on collaborative models in increasing community capacity as an effort to mitigate earthquake and tsunami disasters. In order to achieve this goal, the author conducted literature searches in various sources such as scientific journals and research databases. The research method used was a systematic literature review with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach, where the author identified relevant inclusion and exclusion criteria for selecting articles to be reviewed and had been published in the Scopus database between 2012 and 2022. Based on the results of a literature review, it was found that earthquake and tsunami disaster mitigation involves various actors and stakeholders, including government, academic institutions, local communities, and non-governmental organizations. Developing capacity training programs and increasing public awareness about earthquake and tsunami disasters are key factors in increasing community capacity in facing and reducing disaster risks. The application of information and communication technology has also proven effective in increasing the accessibility of information and communication that can be used by the community in emergencies, as well as community participation in planning and implementing disaster mitigation measures